Relación entre los factores de gestión y proceso de formación profesional en un instituto superior tecnológico público en la Región Callao - Baluarte Maticorena, Jaime Armando (2010)
The purpose of this study was to identify the factors that influence the management in the process of comprehensive training in the Public Technology Institute Simon Bolívar. The research is descriptive correlational study with a quantitative approach and a non-experimental design. The research variables are factors of management and comprehensive training process. The samples are 38 teachers of the school, is a questionnaire of 93 questions to each participant. From the results states that there are significant correlations between variables and their respective dimensions. The conclusion reached was that it complies with the general hypothesis that tells us most decisive factors in the management, which contribute to the process of training. Being the most significant factors two relationships. The relationship of planning and curriculum structure with 0769, the relationship organization and teaching methods with 0717. We consider significant expense.